Development and trainability of agility in youth: A systematic scoping review - Thieschäfer, Lutz; Büsch, Dirk (Frontiers in Sports and Active Living, 2022)
Background: Agility is acknowledged as a crucial factor of performance in various open skill sports in both adult and youth athletes. However, despite its significance for sports performance the development and the trainability of agility are under-researched within the pediatric literature. A systematic scoping review was considered most appropriate to provide researchers and practitioners with an overview of the current body of literature approaching agility in youth. Objectives: The objectives of this scoping review were to map the extent, range, and nature of existing evidence regarding trainability and ‘natural’ development of agility and to summarize corresponding study results. Methods: The scoping review protocol was pre-registered at Open Science Framework. Systematic searches were conducted using the databases PubMed, Scopus, ProQuest, Web of Science, SURF, and SPONET to identify sources covering agility in youth. Among other inclusion criteria, only references applying unplanned agility concepts were included. Results: Ultimately, 41 reports were included comprising 23 observational studies, 14 experimental studies, and 4 references of secondary research. A total of 3,087 subjects were assessed in the included studies. Subject groups were predominantly male, above 10 years of age, and soccer athletes. Outcomes of observational studies indicate an effect of age and maturation on agility performance resulting in a non-linear ‘natural’ development of agility. Furthermore, relationships between contributing perceptual-cognitive factors and agility performance tend to increase with progressing age, whereas relationships between physical factors and agility performance diminish. Evidence of training studies suggests that agility is trainable in youth, albeit with various underlying mechanisms. Conclusions: This systematic scoping review is the first mapping of the body of literature about agility in youth. It outlines the current evidence base, reveals research gaps, and points out future directions to support researchers and practitioners in this field. Although, increasing research activity in this field is discernible, agility research in youth is still in its infancy. Considering the significance of agility for sports performance, future research is postulated to design evidence-based strategies for long-term agility development in young athletes.